Features of the diet in patients with IgA nephropathy and celiac antibodies in the blood - Mariya E. Mantsaeva; Alexey G. Borisov; Sergey V. Chernavsky; Anatoly A. Stremoukhov (Лечащий Врач)
Background. This article highlights the most important nutritional issues for patients with IgA nephropathy associated with a high titer of celiac antibodies in the blood. The importance of therapeutic nutrition, which is part of the nephroprotective strategy as an integral part of the therapy of nephrological patients, is emphasized. The release of certain clinical practical recommendations of KDOQI (2020) once again emphasized the great importance of non-drug exposure for effective therapy of kidney diseases of various etiologies.Objective. To adapt therapeutic nutrition as a component of a nephroprotective strategy for patients with IgA nephropathy associated with a high titer of celiac antibodies in the blood.Results. Based on convincing data from the world literature, which are consistent with the results of our own research confirming the association of the above conditions (even in the absence of clinical manifestations of enteropathy), the effectiveness of the gluten-free diet in the complex treatment of IgA nephropathy, the therapeutic diet for this category of patients has been adapted according to the necessary chemical composition and energy value.Conclusion. Nutrition modification is an essential element of the complex therapy of nephrological patients. An individual approach to the selection of dietary therapy, including gluten elimination, will not only reduce the immunological activity of the main glomerular disease, but also, possibly, slow down the rate of progression of chronic kidney disease, delaying the development of terminal renal failure and increasing the reserve capacity of the kidneys.